2017
DOI: 10.1007/s00436-017-5660-2
|View full text |Cite
|
Sign up to set email alerts
|

A modified method for molecular identification of Baylisascaris transfuga in European brown bears (Ursus arctos)

Abstract: Baylisascaris transfuga is a roundworm that has been reported worldwide in most bear species. In mammals and possibly humans, the larvae of B. transfuga can migrate in the tissues of aberrant hosts with larva migrans syndrome. The current study was performed to identify B. transfuga in faecal samples from free-ranging brown bears in the Tatra Mountains National Park in southern Poland. A commercial kit was used to extract genomic DNA directly from faecal samples. Additionally, a Chelex resin-based technique wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Regular monitoring for sanitation and cleaning is necessary to minimize the risk. Zoos also need to take measures to exclude rodents such as rats and mice from food storage and preparation areas, as those rodents can serve as a reservoir host of many zoonotic helminths such as Baylisascaris spp., Toxocara sp., hookworms, and Capillaria hepatica [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regular monitoring for sanitation and cleaning is necessary to minimize the risk. Zoos also need to take measures to exclude rodents such as rats and mice from food storage and preparation areas, as those rodents can serve as a reservoir host of many zoonotic helminths such as Baylisascaris spp., Toxocara sp., hookworms, and Capillaria hepatica [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Humans, especially zoo staff and trappers, can be infected from a contaminated environment. In humans, Baylisascaris larvae may cause ocular and visceral larva migrans , which may become fatal when larvae invade the central nervous system [ 22 ]. Other important potentially zoonotic parasites identified in this study were Toxocara spp.…”
Section: Discussionmentioning
confidence: 99%
“…Baylisascaris transfuga (Nematoda: Ascarididae) is the dominant endoparasite in brown bears for the Historia naturalis bulgarica 44 (2022) past few years in various countries like Slovakia, Romania, Poland and Italy (Borka-Vitalis et al, 2017;De Ambrogi et al, 2011;Gawor et al, 2017;Orosova et al, 2016;Štrkolcova et al, 2018). It is also the leading nematode species in European wild bears (Rigg & Adamec, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated the diagnostic capacity of molecular techniques, based on DNA amplification of parasites from different types of biological samples, such as Ancylostoma caninum, Ancylostoma braziliense and Baylisascaris transfuga isolated from feces (Gawor et al, 2017;Oliveira-Arbex et al, 2016;), Trichinella spp. in samples of muscle (Marucci et al, 2013) and Angiostrongylus vasorum, Dirofilaria immitis and Dirofilaria repens from blood samples (Albonico et al, 2013;Jefferies et al, 2009).…”
Section: Introductionmentioning
confidence: 99%